Control of pests and weeds by natural enemies : - Van Driesche, Roy. (Blackwell Pub, 2008)
This book offers a multifaceted yet integrated discussion on two major applications of biological control: permanent control of invasive insects and plants at the landscape level and temporary suppression of both native and exotic pests in farms, tree plantations, and greenhouses. Written by leading international experts in the field, the text discusses control of invasive species and the role of natural enemies in pest management.